Best Answer

7n - 2 + 3n + 4 = 7n + 3n - 2 + 4 = 10n + 2 which can be simplified to 2(5n +1)

Q: 7n - 2 plus 3n plus 4 equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

Gather like terms. The - 2 and 4; the 7n and 3n. 7n - 2 + 3n + 4 = 10n + 2

All you do is look for like terms such as 7n and 3n; 2 and 8 Then you do 7n+3n=10 n And ........... 2-8=-6 The answer is 10n-6 if you still dont get it contact me(:

9n-2=7n+50 7n+9n=50+2 16n=52 n= 3.25

10n + 3 = 7n + 53n = 2n = 2/3

3n+2+3n+2=6n+4

Related questions

10n+2

22n + 2.

Gather like terms. The - 2 and 4; the 7n and 3n. 7n - 2 + 3n + 4 = 10n + 2

All you do is look for like terms such as 7n and 3n; 2 and 8 Then you do 7n+3n=10 n And ........... 2-8=-6 The answer is 10n-6 if you still dont get it contact me(:

3n + 4n = -14 7n /7 = -14 /7 n = -2

7n + 2 = 4n + 17Subtract 2 from each side:7n = 4n + 15Subtract 4n from each side:3n = 15Divide each side by 3:n = 5

m + 3n = 7n = -2017n = -201n = -201 / 7n = -28.71m + 3n = -201m + 3(-28.31) = -201m - 86.14 = -201m = -201 + 86.14m = -115So the final answer will be, m = -115 and n = -28.71I hope this makes sense. :)

(10, 2)

9n-2=7n+50 7n+9n=50+2 16n=52 n= 3.25

10n + 3 = 7n + 53n = 2n = 2/3

2 - 7n = 6therefore 7n = 2 - 6 = -4 and so n = -4/7 Then 5m + 7n = 6.4 becomes 5m - 4 = 6.4 so that 5m = 10.4 and then m = 10.4/5 = 2.08

3 + 3n = 9 + 2n + 4n n = -2